ENVIRONMENTAL ANALYSIS THROUGH SURVEY TESTIMONY AT THE ENVIRONMENT OF THE CEARÁ-MIRIM RIVER, EXTREMOZ/RN - Victor da Silva Araújo, Hudson; Manoel Silva Sales, Jefferson; Farkatt Tabosa, Werner (Journal of Interdisciplinary Debates, 2021)
The Ceará – river is one of the main rivers of Rio Grande do Norte, its source is in the municipality of Lages and its mouth that is located in the community of Barra do Rio, municipality of Extremoz / RN. Its mouth is embedded in a mangrove ecosystem, which is a nursery of species of marine animals, used for feeding and reproduction. The mangrove is a source for riparian communities, as a way of subsistence, however, this process does not occur in a sustainable way and are often degraded. Besides these actions, there is an irregular occupation of the area, as well as deforestation and diversion of the course of the river to establish shrimp farming tanks, which continues to attack and accelerate the sedimentation of the area, in order to identify environmental problems in the region, we used the sounding technique for an evaluation.